Exploring the synergies between focused ethnography and integrated knowledge translation - Jennifer Baumbusch; Sarah Wu; Sandra B. Lauck; Davina Banner; Tamar O'Shea; Leslie Achtem (BMC, 2018)
Abstract Background Issues with the uptake of research findings in applied health services research remain problematic. Part of this disconnect is attributed to the exclusion of knowledge users at the outset of a study, which often results in the generation of knowledge that is not usable at the point of care. Integrated knowledge translation blended with qualitative methodologies has the potential to address this issue by working alongside knowledge users throughout the research process. Nevertheless, there is currently a paucity of literature about how integrated knowledge translation can be integrated into qualitative methodology; herein, we begin to address this gap in methodology discourse. The purpose of this paper is to describe our experience of conducting a focused ethnography with a collaborative integrated knowledge translation approach, including the synergies and potential sources of discord between integrated knowledge translation and focused ethnography. Methods We describe the specific characteristics and synergies that exist when using an integrated knowledge translation approach with focused ethnography, using a research exemplar about the experiences of frail, older adults undergoing a transcatheter aortic valve implantation. Results Embedding integrated knowledge translation within focused ethnography resulted in (1) an increased focus on the culture and values of the context under study, (2) a higher level of engagement among researchers, study participants and knowledge users, and (3) a commitment to partnership between researchers and knowledge users as part of a larger programme of research, resulting in a (4) greater emphasis on the importance of reciprocity and trustworthiness in the research process. Conclusions Engaging in integrated knowledge translation from the outset of a study ensures that research findings are relevant for application at the point of care. The integration of integrated knowledge translation within focused ethnography allows for real-time uptake of meaningful and emerging findings, the strengthening of collaborative research teams, and opportunities for sustained programmes of research and relationships in the field of health services research. Further exploration of the integration of knowledge translation approaches with qualitative methodologies is recommended.